Kontribusi Pengawas Madrasah terhadap Kinerja Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Belajar di MTSN 1 Bone - Septiana, Septiana (JURNAL AL-QAYYIMAH, 2019)
This article is about the contribution of Madrasah supervisor to the performance of Islamic education teachers in improving learning quality at MTSN 1 Bone. This research is included in the field research category using qualitative research. The approach used in writing theses is normative theological approaches, paedagogical approaches, and managerial approaches. By using the interview guidelines, observation guides and documentation tools, the collected data will be processed and the data processing is done by reducing, data presentation (display data), and verification/withdrawal of conclusions. The final step is analyzing with qualitative descriptive analysis. The results showed that the Madrasah's contribution to the performance of teachers of Islamic Studies in MTsN 1 Bone, analyzed the various problems of PAI teachers, and helped PAI teachers to solve problems in relation With various activities in the learning process. Through this oversight, PAI teachers are expected to find ways to improve their performance and to resolve issues faced in the administration, teaching and learning programs, and internal problems that sometimes become obstacles For the PAI teacher itself. Supervision in the Madrasah is done to develop a better learning situation through teacher coaching and improvement of teacher's performance learning quality. Further supervision is also interpreted as a process of monitoring and evaluation activities to ensure that all educational activities in the Education unit are carried out as planned and also an activity to correct and Fix when there is an aberration that will interfere with the achievement of objectives. For that KONTRIBSI the supervisor is very important in helping to solve the learning problems experienced by the teacher. Performance teacher of PAI subjects in improving the quality of learning in MTsN 1 Bone is good enough. Supervision performed by the supervisor and the head of the Madrasah brings a positive thing. One of them affects the understanding and skill of teachers in using and making learning media. But in terms of learning administration and teaching program activities, it is still needed guidance by the supervisor.Artikel ini adalah tentang kontribusi pengawas Madrasah terhadap kinerja guru pendidikan Islam dalam meningkatkan kualitas pembelajaran di MTSN 1 Bone. Penelitian ini termasuk dalam kategori penelitian lapangan menggunakan penelitian kualitatif. Pendekatan yang digunakan dalam penulisan tesis ini adalah pendekatan teologis normatif, pendekatan paedagogis, dan pendekatan manajerial. Dengan menggunakan pedoman wawancara, panduan observasi dan alat dokumentasi, data yang dikumpulkan akan diproses dan pengolahan data dilakukan dengan mengurangi, penyajian data (menampilkan data), dan verifikasi / penarikan kesimpulan. Langkah terakhir adalah menganalisis dengan analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa kontribusi Madrasah terhadap kinerja guru Studi Agama Islam di MTsN 1 Bone, menganalisis berbagai masalah guru PAI, dan membantu para guru PAI untuk memecahkan masalah dalam kaitannya dengan berbagai kegiatan dalam proses pembelajaran. Melalui pengawasan ini, guru PAI diharapkan menemukan cara untuk meningkatkan kinerja mereka dan untuk menyelesaikan masalah yang dihadapi dalam administrasi, program pengajaran dan pembelajaran, dan masalah internal yang kadang-kadang menjadi hambatan bagi guru PAI itu sendiri. Pengawasan di Madrasah dilakukan untuk mengembangkan situasi belajar yang lebih baik melalui pembinaan guru dan peningkatan kualitas pembelajaran kinerja guru. Pengawasan lebih lanjut juga ditafsirkan sebagai proses kegiatan pemantauan dan evaluasi untuk memastikan bahwa semua kegiatan pendidikan di unit Pendidikan dilaksanakan sesuai rencana dan juga kegiatan untuk memperbaiki dan Memperbaiki ketika ada penyimpangan yang akan mengganggu pencapaian tujuan. Untuk itu KONTRIBSI pengawas sangat penting dalam membantu menyelesaikan masalah pembelajaran yang dialami oleh guru. Kinerja guru mata pelajaran PAI dalam meningkatkan kualitas pembelajaran di MTsN 1 Bone cukup baik. Pengawasan yang dilakukan oleh pengawas dan kepala Madrasah membawa hal positif. Salah satunya mempengaruhi pemahaman dan keterampilan guru dalam menggunakan dan membuat media pembelajaran. Namun dalam hal kegiatan administrasi pembelajaran dan program pengajaran, masih diperlukan bimbingan oleh penyelia.